Bilateral Keratocystic Odontogenic Tumor Invading Maxillary Sinuses: A Case Report - Mohajerani, Hasan; Pakravan, Amir Hosein; Aghdashi, Seyed Farzad; Nahvi, Golnaz; Motamedian, Saeed Reza (Regeneration, Reconstruction & Restoration (Triple R), 2016)
Keratocystic odontogenic tumor (KCOT) is an odontogenic tumor which has the highest rate of recurrence. This report describes a rare case of bilateral ciliated epithelium-lined odontogenic keratocyst in the maxilla of a 15-year-old male. Panoramic radiography showed two lytic lesions on both sides of the maxilla associated with impacted third molars. Computerized tomography image revealed the involvement of both maxillary sinuses by the lesion which was destroying both sinuses’ floors and posterior walls. Histopathologically, the keratinized epithelial-lined cyst of OKC was changed to a ciliated columnar hyperchromatic epithelium, suggesting the fusion of both these epithelia rather than a metaplastic transformation. The patient was treated by surgical enucleation of the cyst and was followed for one year. In this case report the biological behaviour of odontogenic keratocysts and its treatment options are discussed.